A Longitudinal Study of Spontaneous Gut Decolonization of Carbapenem-resistant Gram-negative Bacteria in Neonatal and Pediatric Patients. Issue 8 (13th July 2022) - Darda, Violetta-Magdalini; Iosifidis, Elias; Antachopoulos, Charalampos; Kirvasilis, Fotis; Zarras, Charalampos; Simitsopoulou, Maria; Papakonstantinou, Eugenia; Agakidou, Eleni; Sdougka, Maria; Roilides, Emmanuel
Abstract : Background: Antibiotic exposure may convert gut microbiome to reservoir of resistant organisms, including carbapenem-resistant Gram-negative bacteria (CRGNB). Little is known about natural history of spontaneous CRGNB decolonization of neonates/children and their risk to develop CRGNB infections. Methods: Patients hospitalized in a tertiary care hospital (1 days to 16 years) found to be CRGNB colonized in weekly surveillance cultures during hospitalization (January 2018 to December 2019) were prospectively followed after discharge with monthly rectal cultures for 12 months after colonization until decolonization (3 consecutive negative rectal cultures, ≥1 week apart). Patient demographics, clinical characteristics and CRGNB infections were recorded. Polymerase chain reaction for carbapenemases was performed in patients colonized, after 3 negative cultures, at the day of the last negative and the day of the first new positive culture. Results: One-hundred thirty patients (median age, 1.3 months; lower-upper quartile values, 0.8–6.9 months) were studied including 66 neonates (median age, 12.6 days; Q1–Q3, 5–18.5 days). Among patients >30 days old, 51.6% achieved decolonization within 6 months, and among neonates, 91% achieved decolonization within 6 months. By 12th month, 89% of >30 days and 100% of neonates were decolonized. Forty-four (33.9%) patients (59% >30 days and 9% neonates) developed CRGNB infection(s), mainly pneumonia (25%) and bloodstream infection (20.5%). Prolonged colonization (odds ratio [OR], 7.75; 95% confidence interval [CI], 2.10–28.58), duration of broad-spectrum antibiotic use (OR, 1.22; 95% CI, 1.11–1.34) and parenteral nutrition (OR, 4.53; 95% CI, 1.14–17.94) were associated with the development of CRGNB infection. Two patients (1.5%) were found by polymerase chain reaction colonized after 3 negative cultures. Conclusions: Spontaneous decolonization occurs in most CRGNB colonized >30 days and all neonates within 12 months. One-third of colonized patients develop CRGNB infection(s). These findings may help optimize duration of contact precautions and empirical antimicrobial therapy for CRGNB colonized pediatric patients.